Genes involved in the transforming growth factor beta signalling pathway and the risk of intracranial aneurysms. Issue 6 (16th May 2008) - Ruigrok, Y M; Tan, S; Medic, J; Rinkel, G J E; Wijmenga, C
Abstract : Background and purpose: The 19q13.3 locus for intracranial aneurysms (IA) partly overlaps with the 19q13 locus for abdominal aortic aneurysms (AAA). A common genetic risk factor located in this locus for the two aneurysm types seems plausible. The transforming growth factor beta (TGF-β) signalling pathway plays a role in aortic aneurysms but may also play a role in aneurysms in general. In the combined region of the 19q13 loci for IA and AAA we identified two candidate genes that are both involved in the TGF-β signalling pathway: hepsin ( HPN ) and the latent transforming growth factor beta-binding protein 4 ( LTBP4 ). We hypothesised that single nucleotide polymorphisms (SNP) in the HPN and LTBP4 genes are associated with IA. Methods: We analyzed all the common variations using tag SNP in the HPN and LTBP4 genes for association with IA in 390 patients and 642 controls in the Dutch population. Six tag SNP in the HPN gene and five tag SNP in the LTBP4 gene were genotyped. Results: No differences in SNP frequency were observed for both the HPN and LTBP4 gene between patients and controls. Conclusion: Our findings suggest that variations in or near the HPN and LTBP4 genes do not play a role in the susceptibility to IA in the Dutch population.